Goodbye to All That. Issue 2 (April 2015) - Mitchell, Austin
Abstract This article is the retirement reflections of an MP of thirty‐eight year's standing. The story is mainly one of the decline of the Commons, a decline in the number of 'big beasts' and in the calibre of members and the quality of debates to the level of five‐minute harangues and the custard pie‐throwing of Prime Minister's Question Time. The House has lost its functions of staging the national debate and checking the executive to the media but has gained a new role as a national audit of government's performance and policies through the select committee system. MPs are working harder. Fewer now have outside jobs. They are more focused on their constituencies and though they have fewer powers there, and nationally more and better staff, they also have less respect and less influence. Personally, the end of what has been a long‐fighting national retreat from social democracy has been a rear‐guard action against the emergence of a colder, harder, neoliberal world. Retirement means relegation to watching that from the sidelines, not ringside.